2019
DOI: 10.1177/2333794x19835645
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Pediatric Attention Deficit Hyperactivity Disorder on Family Stress and Well-Being: Development of the IMPACT 1.0 Scale

Abstract: Medications may lessen core symptoms of attention deficit hyperactivity disorder (ADHD), yet families continue to report stress and have a low quality of life. Primary care providers manage almost half of all children with ADHD but do not have a brief measure to assess ADHD impacts on family in the context of everyday family life. The IMPACT (Impact Measure of Parenting-Related ADHD Challenges and Treatment) 1.0 Scale was codeveloped with input from parent advisors and administered to 79 parents of children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The toll taken on families and caregivers is often what prompts caregivers to seek treatment for their child (Angold et al 1998). If a medication improves ADHD symptoms in children but caregivers continue to experience strain, this may affect the continuity of treatment or caregiver satisfaction with treatment (Bauer et al 2019). This might be especially important for parents with ADHD, as the burden of caring for a child with ADHD is even more exacerbated (Chronis-Tuscano et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The toll taken on families and caregivers is often what prompts caregivers to seek treatment for their child (Angold et al 1998). If a medication improves ADHD symptoms in children but caregivers continue to experience strain, this may affect the continuity of treatment or caregiver satisfaction with treatment (Bauer et al 2019). This might be especially important for parents with ADHD, as the burden of caring for a child with ADHD is even more exacerbated (Chronis-Tuscano et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These studies found that children diagnosed with ADHD experienced their sibling relationships as more negative and conflict-laden compared to healthy control groups (Kouvava & Antonopoulou, 2020; Mikami & Pfiffner, 2008). A recent study exploring the impact of child ADHD on family stress and well-being in everyday life further identified the sibling domain as a key source of daily family strain, with higher levels of sibling negativity being related to increased hyperactive–impulsive symptoms (Bauer et al, 2019). Analogous to the parent–child relationship, studies examining sibling dyads in which one child suffers from ADHD indicate that the association with sibling conflict is particularly strong in the context of elevated hyperactivity–impulsivity symptoms, as opposed to inattention (Mash & Johnston, 1983).…”
Section: A Transactional Family Systems Approach To Developmental Psy...mentioning
confidence: 99%